Basic Anesthesiology Examination review - Williams, George (George W.); Williams, Erin (Erin Scott) ([New York] : Oxford University Press, 2016)
Containing concise content review, board-style questions and answers with explanations, and key references, this book is a high-yield, efficient study aid for residents preparing for the Basic Anesthesiology Examination.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on January 12, 2016).
Keywords: Anesthesiology -- Examinations, questions, etc